2020
DOI: 10.3389/fnmol.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Binding to Phosphorylated PSD-95 Regulates the Number of Functional Excitatory Synapses

Abstract: The post-synaptic density protein 95 (PSD-95) plays a central role in excitatory synapse development and synaptic plasticity. Phosphorylation of the N-terminus of PSD-95 at threonine 19 (T19) and serine 25 (S25) decreases PSD-95 stability at synapses; however, a molecular mechanism linking PSD-95 phosphorylation to altered synaptic stability is lacking. Here, we show that phosphorylation of T19/S25 recruits the phosphorylation-dependent peptidyl-prolyl cis-trans isomerase (Pin1) and reduces the palmitoylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This mechanism may explain a loss of synaptic surface PSD-95 and AMPAR during chemically induced LTD in cultured rat neurons [ 279 ]. A recent study showed that phosphorylation-dependent peptidyl-prolyl cis – trans isomerase (Pin1) binding to phosphorylated PSD-95 results in decreased palmitoylation of PSD-95, which subsequently led to a loss in the number of dendritic PSD-95 clusters, increased AMPAR mobility and a decreased number of functional excitatory synapses [ 280 ]. This data may shed light on the intertwined function of phosphorylation and palmitoylation of PSD-95 in the regulation of synaptic plasticity.…”
Section: Palmitoylation Of Ampar and Its Associated Scaffold Proteinsmentioning
confidence: 99%
“…This mechanism may explain a loss of synaptic surface PSD-95 and AMPAR during chemically induced LTD in cultured rat neurons [ 279 ]. A recent study showed that phosphorylation-dependent peptidyl-prolyl cis – trans isomerase (Pin1) binding to phosphorylated PSD-95 results in decreased palmitoylation of PSD-95, which subsequently led to a loss in the number of dendritic PSD-95 clusters, increased AMPAR mobility and a decreased number of functional excitatory synapses [ 280 ]. This data may shed light on the intertwined function of phosphorylation and palmitoylation of PSD-95 in the regulation of synaptic plasticity.…”
Section: Palmitoylation Of Ampar and Its Associated Scaffold Proteinsmentioning
confidence: 99%
“…Changes in hippocampal synaptic plasticity caused by androgen deficiency include abnormal expression of synapse-associated proteins ( Zhao et al, 2018 ), decreased dendritic spine density ( Leranth et al, 2003 ), and decreased synaptic transmission efficiency ( Cooke and Woolley, 2009 ). PSD95, a scaffold protein, is primarily located in the excitatory glutamic energy postsynaptic membrane ( Delgado et al, 2020 ). PSD95 is a key protein that promotes synapse maturation and maintains the stability of dendritic spines ( Ampuero et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…180 PSD-95: Postsynaptic density protein-95 (PSD-95) is a membrane-associated scaffold protein that plays a central role in the development of synapse development, number, stabilization, and function. [192][193][194] A well-studied action of PSD-95 is the anchoring AMPA and NMDA receptors in the postsynaptic terminal, which regulates neurotransmission by glutamate. 195 Not surprisingly, altered PSD-95 function has been implicated in epilepsy.…”
Section: Potential Common Effectorsmentioning
confidence: 99%